IMPLEMENTASI INOVASI BARU PEMANFAATAN SINGKONG DAN LIMBAH KULIT SINGKONG - dutufiyah, siti; Setyawan, Wahyu Aris (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2021)
The study was done with the aim of identifying waste products Cassava skin for the crisps and new innovation in cassava fuel the advantage of the manufacture of chips is to give people a picture that the cassava sheath can be processed into a nutritious food economical and has many health benefits, cassava skin contains calcium, iron, vitamins B and C, and amylium, The leaves contain Vitamins A, B1, and C, Calcium, Calories, Protein, fat, Charcoal Hydrated, and iron. While the bark of the stem, Contains Tannin, Peroxide enzymes, Glycoside, and Calcium oxalate. The product of these innovations is the cassava skin and grill nozzles cassava al muttaqin, wich will be awarded copyright for superior products on the foundation. Pondok Pesantren Sabilul Muttaqin